Concurrent chemoradiotherapy combined with nimotuzumab in stage III–IVa nasopharyngeal carcinoma: a retrospective analysis - Cai, Zhuochen; Chen, Dongni; Qiu, Wenze; Liang, Chixiong; Huang, Yingying; Zhou, Jiayu; Zhan, Zejiang; Xiang, Yanqun; Guo, Xiang; Lv, Xing (Journal of cancer research and clinical oncology, 2023)
Purpose The efficacy and safety of nimotuzumab (NTZ) added to concurrent chemoradiotherapy (CCRT) were investigated in patients with stage III–IVa nasopharyngeal carcinoma (NPC). Methods Patients with stage III–IVa NPC treated with CCRT, with or without NTZ, were screened between January 2015 and December 2017. We compared patients’ overall survival (OS), progression-free survival (PFS), locoregional recurrence-free survival (LRFS), and distant metastasis-free survival (DMFS) between different therapeutic regimens. Propensity score matching (PSM) was applied to reduce the selection bias. Nomogram models were developed to predict the survival of CCRT with or without NTZ. Results Four hundred and twenty-six patients were included after PSM, with 213 patients in each regimen. Compared with NPC patients receiving CCRT alone, patients who received NTZ plus CCRT treatment had significantly better OS (5 year OS, 76.1 vs. 72.3%, P = 0.004), PFS (5 year PFS, 73.2 vs. 69.0%, P = 0.002), and LRFS (5 year LRFS, 73.2 vs. 69.0%, P = 0.028). A multivariate Cox regression analysis demonstrated that, compared with receiving CCRT alone, NTZ plus CCRT was an independently positive factor for OS, PFS, and LRFS. No significant difference was observed in the major toxicities between the two treatments (all P > 0.05). In addition, the nomogram presented good accuracy for predicting the prognosis of NPC patients. Conclusion CCRT combined with NTZ presented favorable clinical outcomes for stage III–IVa NPC patients with good tolerance and similar toxicity compared to CCRT alone. A prospective, randomized clinical trial is essential to validate the current findings.